A snapshot of management practices and nutritional recommendations used by feedlot nutritionists in Brazil - Millen, D. D. [UNESP]; Pacheco, R. D. L. [UNESP]; Arrigoni, Mario de Beni [UNESP]; Galyean, M. L.; Vasconcelos, J. T. (Amer Soc Animal Science, 2009)
Feedlot consulting nutritionists were invited to participate in a survey of feedlot nutritional and management practices in Brazil. Thirty-one nutritionists completed the survey on a Web site that was designed for collection of survey data. The survey consisted of 94 questions that included general information (n = 10); commodity information (n = 12); and questions about the use of coproducts (n = 5), roughage source and levels (n = 5), finishing diet adaptation methods (n = 7), supplements and micronutrients (n = 8), feed mixers (n = 6), feeding management (n = 3), cattle management and type of cattle fed (n = 16), formulation practices (n = 17), information resources used for nutritional recommendations (n = 2), and 2 additional questions. One final question addressed the primary challenges associated with applying nutritional recommendations in practice. The number of animals serviced yearly by each nutritionist averaged 121,682 (minimum = 2,000; maximum = 1,500,000; mode = 120,000; total = 3,163,750). Twenty-two respondents (71%) worked with feedlots that feed less than 5,000 animals/yr. Labor, along with availability and precision of equipment, seemed to be the main challenges for the nutritionists surveyed. Most of the nutritionists surveyed used TDN as the primary energy unit for formulation. More than 50% of the clients serviced by the 31 nutritionists did not manage feed bunks to control the quantity of feed offered per pen, and 36.6% fed cattle more than 4 times daily. The NRC (1996) and Journal of Animal Science were the most used sources of information by these nutritionists. Overall, general practices and nutritional recommendations provided by the 31 nutritionists surveyed were fairly consistent. Present data should aid in development of new research, future National Research Council models, and recommendations for Brazilian feeding systems in which Bos indicus cattle predominate.
Keywords: beef cattle; Brazil; feedlot; nutritionist; recommendation